Towards Interprofessional Education and Collaboration to Improve Students’ Competences - RR Sri Endang Pujiastuti; Emy Rianti; Oktia Woro Kasmini Handayani; Irma Muslimin; Madiha Mukhtar; Runjati; Sherly Meitasari; Ike Puspitaningrum (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Interprofessional education collaboration (IPE/C) among undergraduate students is a pivotal learning experience to build comprehensive competencies in a better understanding of communication, teamwork, and the roles of different professions. This study aimed to investigate the interprofessional education collaboration among nursing students in clinical nursing practices, with a descriptive quantitative research design. A total of 69 undergraduate nursing students participated who had experienced interprofessional practices in 2024. Data were collected using a structured, selfadministered questionnaire adopted from the Psychometric Evaluation of Interprofessional education collaboration Competency Tool (PEIEC). The result of this study showed the highest professional identity, 43 (62%), and other competences 38% regarding teamwork, roles, responsibility, and communication. The findings revealed generally positive exploring very good competences (54%) for doing team collaboration and good competences for others, including communication (26%) and 20% (professional identity). IPE/C has been widely studied and recognized for its benefits in healthcare education and practice. IPE/C has been reported as pivotal in preparing students for the health workforce, where teamwork is an essential competency required for practice. Numerous studies have demonstrated that IPE/C fosters interprofessional collaboration, reduces barriers and preconceptions among different healthcare student groups, and enhances professional competencies. In conclusion, the Interprofessional education collaboration is essential to advancing competencies, enhancing collaboration, and contributing to better patient care outcomes